Pygmy grasshoppers (Orthoptera: Tetrigidae) from Bạch Mã National Park, central Vietnam - Storozhenko, Sergey Yu.; Tan, Ming Kai; Vu, Trung Thanh; Le, Cuong Viet Canh; Pham, Thai Hong (Zootaxa, 2023)
A list of 10 species from three subfamilies of Tetrigidae from Bạch Mã National Park in the province of Thừa Thiên-Huế, Vietnam is presented here. Eight of which are new for the national park. Among these, two new species are described: Miriatroides luna Tan & Storozhenko, sp. nov. and Rhopalina bachma Tan & Storozhenko, sp. nov. New synonymy is proposed: Systolederus cinereus Brunner von Wattenwyl, 1893 = Systolederus ridleyi Hancock, 1909, syn. nov. Three species are also recorded in Vietnam for the first time: Tegotettix bufocrocodil (Storozhenko & Dawwrueng, 2015) previously known from Thailand and Cambodia, Zhengitettix albitarsus Storozhenko, 2013 so far considered as endemic to Thailand, and Systolederus cinereus widely distributed in Southeast Asia.